IDENTIFIKASI DAN INTENSITAS SERANGAN HAMA PADA ANAKAN SENGON (Paraserianthes falcataria (L).Nielsen ) DI KAWASAN HUTAN DENGAN TUJUAN KHUSUS TUMBANG NUSA KALIMANTAN TENGAH (Identification and Intensity of Pests that Attack Sengon Saplings in the KHDK Tumba: Syariffudin 1), Eritha K.Firdara 2), Patricia E.P. 2) - Admin JHT (Jurusan Kehutanan, Fakultas Pertanian Universitas Palangka Raya, 2018)
ABSTRACTSelection Sengon on an industrial scale is an appropriate choice to be prioritized for theDevelopment of Industrial Plantation Forest (IUPHHK-HTI). In 1989 Balai Besar Selulosa(BBS) in Bandung have researched pulp sengon derived from wood raw material for newsprintand other printing papers such as copier paper. Forest areas with special purpose is designated forthe purpose of research and development, education and training as well as cultural and religiousinterest of the local, in accordance with the mandate of law No. 41, 1999 without altering thefunction of the area. Sengon known by the botanical name as Paraserianthes falcataria,including in fabaceae family. Sengon (Paraserianthes falcataria) can grow on poor soils and alittle nest, dry soil, wet, or rather salty. The purpose of this research is for identify and knowingthe intensity of pests that attack in puppies sengon (Paraserianthes falcataria) at the nursery inKHDTK (Kawasan Hutan Dengan Tujuan Khusus) Tumbang Nusa, District of jabiren CentralKalimantan.This Research was conducted in the nursery area located in Kawasan Hutan DenganTujuan Khusus (KHDTK), Tumbang Nusa, District of jabiren Central Kalimantan for threemonths. The object being observed in this research is puppies sengon (Paraserianthes falcataria)which is in the area of the nursery with 3600 puppies sengon in the seedbed and seedling peststhat attack on sengon (Paraserianthes falcataria). Results of the study show the identification ofpests that attack pests sengon saplings in the nursery area for research there are two kinds of pestsare locusts and caterpillars. The frequency and intensity of pest attacks are 0,25 % and 0,18%with the level of damage including healty criteria. So the amount of frequency and intensity ofattack in puppies sengon are 0,25% and 0,18%.Keywords : Description of sengon, pests attack